Antibiotics in the first year of life and subsequent neurocognitive outcomes. (January 2017) - Slykerman, Rebecca F.; Thompson, John; Waldie, Karen E.; Murphy, Rinki; Wall, Clare; Mitchell, Edwin A.
Abstract: Aim: There may be a link between disruption to the gut microbiota in early life and later neurocognitive outcomes. We hypothesised that antibiotic use in early life is associated with a detrimental effect on later neurocognitive outcomes. Methods: Eight hundred and seventy‐one European mothers and their children enrolled in the Auckland Birthweight Collaborative Study at birth. Information on antibiotic use during the first year of life and between 12 months and three‐and‐a‐half years of age was gathered via maternal interview. Intelligence test scores and measures of behavioural difficulties were obtained when children were three‐and‐a‐half years, seven years and 11 years of age. Results: Antibiotic use in the first year of life was reported in 70% of the 526 children with antibiotic data assessed at age three‐and‐a‐half years. Those who had received antibiotics had more behavioural difficulties and more symptoms of depression at follow‐up. Results were consistent across all standardised psychologist administered tests, as well as parent rated, teacher rated and self‐report measures. Conclusion: This study demonstrates an association between antibiotic use in the first year of life and subsequent neurocognitive outcomes in childhood. If confirmed by further research, these findings could have implications for the use of antibiotics for minor illnesses in infancy. Abstract :